Effect of Auriculotherapy on depression in infertile women: A Randomized Clinical Trial - Marjan Ghodrati; Ali Mohammadpour; Ali Khorsand Vakilzadeh; Jahanshir Tavakolizadeh; Fatemeh Hadizadeh Talasaz (Mashhad University of Medical Sciences, 2019)
Introduction: Having a child is a basic need in humans. Infertility can lead to unpleasant outcomes such as depression which is required to identification and appropriate interventions. Acupressure is one of the methods used in the treatment of depression. This study was performed with aim to determine the effect of auriculotherapy on depression in infertile women. Methods: This randomized clinical trial was performed on 70 infertile women referred to Milad Infertility Centre at Mashhad in 2017. The subjects were randomly assigned to two groups of intervention and control. Before the intervention, depression in both groups was measured by Beck questionnaire. Then, in the intervention group, the ear glue was attached in one of the ears at the points of shenmen, anti- depressant and heart, and the patient was asked to press each of the points twice a day and 60 times for a period of one month. No intervention was performed in the control group. Depression was again measured immediately after the intervention and two months later in both groups. Data were analyzed by SPSS software (version 19) and independent t-test, Chi-square and ANOVA with repeated measurement. P<0.05 was considered statistically significant. Results: Depression score had no significant difference in two groups before the intervention (p> 0.05). However, depression scores immediately and two month after the intervention were less in the intervention group than the control group and there was a significant statistical difference between two groups (p <0.001). Conclusion: Considering the presence of depression in infertile patients, auriculotherapy can be used as a non-pharmacological method to reduce depression.